Technology development and field testing: access to credit to allow smallholder dairy farmers in central Kenya to reallocate concentrates during lactation - Romney, Dannie L.; Kaitho, R.; Biwott, J.; Wambugu, M.; Chege, L.; Omore, Amos O.; Staal, Steven J.; Wanjohi, P.; Thorpe, W.R. (International Livestock Research Institute, 2000)
A field trial with smallholder dairy farmers in central Kenya was carried out to study the feasibility of reallocating concentrates as a means of increasing the profitability of milk production. Researchers designed the trial with extension officers, dairy co-operative and feed company staff to ensure that all stakeholders and key players were involved. Central to the design was the provision of feed on credit from the dairy co-operative to its members, the volunteer farmers involved in the study. The role of the research team was to present the technology to the farmers and monitor the implementation and impact. Farmers were not constrained in the way they chose to implement the recommendations, but the research team monitored any modifications as well as recording production parameters and characteristics of the farm and feed management systems likely to explain underlying variation.